2014
DOI: 10.1111/cei.12308
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin levels and their potential association with venous thromboembolism and survival in cancer patients

Abstract: SummaryCytokines have been found to be elevated in cancer patients and have been associated with worse prognosis in single tumour entities. We investigated the association of eight different cytokines with venous thromboembolism (VTE) and prognosis in cancer patients. The Vienna Cancer and Thrombosis Study (CATS), a prospective study, includes patients with newly diagnosed tumour or disease progression. Patients with an overt infection are excluded. Study end-points are VTE, death, loss to follow-up or study c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…In our study, those with VTE had significantly higher levels of IL-6 than those who did not have VTE, and this association has not been well studied in cancer patients. 26 In addition, VTE was associated with thrombocytosis (Table 2), which has recently been recognized in the oncology field. 27 Our findings also showed that elevated IL-6 is associated with thrombocytosis, and those with advanced-OCCC had the highest frequency of multiple-site VTE (DVE+PE; 11.3%) compared with the other groups.…”
Section: Discussionmentioning
confidence: 97%
“…In our study, those with VTE had significantly higher levels of IL-6 than those who did not have VTE, and this association has not been well studied in cancer patients. 26 In addition, VTE was associated with thrombocytosis (Table 2), which has recently been recognized in the oncology field. 27 Our findings also showed that elevated IL-6 is associated with thrombocytosis, and those with advanced-OCCC had the highest frequency of multiple-site VTE (DVE+PE; 11.3%) compared with the other groups.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to carcinogenesis, IL-6 contributes to hemostasis 43,44 and vasculopathy 45,46 , and IL-6 genetic variants have been implicated in atherosclerosis 43,47 , hypertension 47 , and cancer-associated thromboembolism 48 . Accordingly, we explored whether IL-6 SNPs could predict bevacizumab toxicity (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Visconti et al (31) demonstrated that elevated IL-6 and IL-10 levels appear to be independently associated with worse prognosis in terms of overall and disease-free survival in cancer patients. Reitter et al (32) reported that elevated levels of IL-6, IL-8 and IL-11 were associated with worse survival of cancer patients. Cheng et al (33) revealed that NPC patients who had high IL-8 levels had significantly shorter overall survival and disease-free survival.…”
Section: Discussionmentioning
confidence: 99%